A NARRATIVE ANALYSIS OF ENGLISH TEACHER’S EXPERIENCES IN TEACHING PUBLIC SPEAKING THROUGH ONLINE LEARNING-BASED EMERGENCY REMOTE TEACHING - Indah Khoirunnisa (Universitas Galuh, 2022)
This article is focused to investigate the way the English teacher prepares, implements and evaluates, what problems are faced, and how to solve problems that occur during the learning activity takes place. The study employed a narrative analysis method to find out the English teachers’ experiences, the problems and its solutions in the implementation of teaching public speaking through online learning based-emergency remote teaching in the Covid-19 pandemic situation. The first result of this study reveals that there are several things that must be considered to carry out learning activities, namely the preparation stage, the implementation stage and the stage for evaluating student learning outcomes. The second result indicates that several problems emerged on its implementation, namely poor internet connections, the lack of student internet quotas, and the problem of direct interaction between teacher and students during virtual meetings. The third result come with the solutions that were found to overcome network problems and internet quotas is to make learning video recordings posted on Google Classroom or Telegram; so students can watch them at a later time after having a good internet connection and sufficient quota, and the provision of Telegram as a forum for indirect interaction between teachers and students outside of direct interaction in virtual meetings.